Clusters of Hantavirus Infection, Southern Argentina - Lázaro, Maria E. (2007)
Person-to-person transmission of a hantavirus was first confirmed during a 1996 outbreak of hantavirus pulmonary syndrome in southern Argentina, where Andes virus is endemic. To identify other episodes of secondary transmission, we reviewed reports of 51 hantavirus infection cases from this region (November 1993–June 2005). Nine clusters involving 20 cases (39.2%) were found. Two patients, who had symptoms 3 weeks after they shared risks for rodent exposure, were considered a cluster. The other 8 clusters each began with an index case, which was almost always fatal, followed 19–40 days later by the illness of >1 person who had close and prolonged contact with the index case-patient. Person-to-person transmission was considered the probable source of these 8 clusters. The probability of initiating secondary cases was 41% for patients who died versus 4% for those who survived (p = 0.005). Interpersonal transmission of Andes virus infection should be considered even when rodent exposure cannot be definitively excluded.